2023
DOI: 10.1001/jamaoncol.2023.1629
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Progression and Toxic Effects After Preoperative Stereotactic Radiosurgery for Patients With Resected Brain Metastases

Abstract: ImportancePreoperative stereotactic radiosurgery (SRS) has been demonstrated as a feasible alternative to postoperative SRS for resectable brain metastases (BMs) with potential benefits in adverse radiation effects (AREs) and meningeal disease (MD). However, mature large-cohort multicenter data are lacking.ObjectiveTo evaluate preoperative SRS outcomes and prognostic factors from a large international multicenter cohort (Preoperative Radiosurgery for Brain Metastases–PROPS-BM).Design, Setting, and Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Early studies demonstrated low rates of LMD after preoperative SRS, sparking large randomized clinical trials (NCT05438212) to further establish the possible benefits of preoperative SRS. 2 , 3 , 5 , 16 It has been postulated that preoperative SRS may reduce LMD rates by treating the lesion prior to potential tumor spillage during surgery, thereby making cellular spread into the leptomeninges unviable. 2 , 3 , 5 , 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated low rates of LMD after preoperative SRS, sparking large randomized clinical trials (NCT05438212) to further establish the possible benefits of preoperative SRS. 2 , 3 , 5 , 16 It has been postulated that preoperative SRS may reduce LMD rates by treating the lesion prior to potential tumor spillage during surgery, thereby making cellular spread into the leptomeninges unviable. 2 , 3 , 5 , 14–16 …”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 This risk provides a rationale for preoperative SRS, which is hypothesized to decrease the risk of LMD, with initial studies demonstrating meningeal disease rates of 5.8% compared with 16% to 21% in the postoperative setting. 48 , 49 , 50 Other potential benefits of preoperative SRS include improved logistics due to not having to coordinate postoperative treatment, earlier initiation of systemic therapy, and ability to treat to doses that are about 20% to 25% lower. 49 , 51 A potential disadvantage of preoperative SRS is the risk of irradiation of benign or primary CNS lesions, which has been reported to occur in 2% to 11% of patients.…”
Section: Case Presentationsmentioning
confidence: 99%